La corte y la sociedad cortesana en el mundo hispánico (siglos XVI-XVIII) - Luzzi, Marcelo; Escamilla González, Iván; Guillén Berrendero, José Antonio (Historia del Mundo Ibérico: Del Antiguo Régimen a las Independencias, 2023)
The court and court society in the Hispanic world (16th-18th centuries): The courtly world has emerged as a propitious intellectual and historiographical space for thinking and writing the history of early modernity. Ever since the renewal of the so-called 'political history,' but also after the perspective of cultural studies, the courtly has become the privileged scenario for the study of the political society of the Modern Age, starting from the analysis of the formation of the different social actors' different political identities in dispute, as well as the tracking of hidden interests in decision-making in order to understand power groups or networks. Similarly, the courtly cannot but be thought of as that singular scenario and/or space of conjunction and indistinction between the political (public) and the economic (private), as well as a locus of identity formation and dispute. In this sense, the study of the Ancien Régime societies cannot ignore the courtly, which is a key element for understanding and analyzing one of the articulating elements of the globality of the European monarchies, particularly the Hispanic monarchy. As this work describes, this global perspective allows us to understand the importance and imprint of the courtly in America. Therefore, the aim is to analyze and understand the court and the courtly world from multiple perspectives. The articles that make up this work problematize the courtly from different geographical spaces, but above all from different intellectual concerns and preoccupations: princely and courtly education, the problem of the King's favorite, the religious, the nobiliary, the place of the feminine in the court or, also, the materiality of the courtly texts and the materiality of the government of the monarchy from the court.